2016
DOI: 10.3390/ma9040225
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Monodispersed Ag-Doped Bioactive Glass Nanoparticles via Surface Modification

Abstract: Monodispersed spherical Ag-doped bioactive glass nanoparticles (Ag-BGNs) were synthesized by a modified Stöber method combined with surface modification. The surface modification was carried out at 25, 60, and 80 °C, respectively, to investigate the influence of processing temperature on particle properties. Energy-dispersive X-ray spectroscopy (EDS) results indicated that higher temperatures facilitate the incorporation of Ag. Hydroxyapatite (HA) formation on Ag-BGNs was detected upon immersion of the particl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(38 citation statements)
references
References 31 publications
1
37
0
Order By: Relevance
“…The as-synthesized BGN have shown apatite-forming ability as reported in our previous study, 44 and hydroxyapatite (HA) can form on BGN after immersion in SBF within 7 days. However, the coating of ZnO QDs on BGN inhibited the bioactivity of particles, as no significant formation of HA could be observed in ZnO-BGN upon immersion in SBF for 14 days according to the FTIR spectrum (Fig.…”
Section: In Vitro Mineralizationsupporting
confidence: 69%
See 1 more Smart Citation
“…The as-synthesized BGN have shown apatite-forming ability as reported in our previous study, 44 and hydroxyapatite (HA) can form on BGN after immersion in SBF within 7 days. However, the coating of ZnO QDs on BGN inhibited the bioactivity of particles, as no significant formation of HA could be observed in ZnO-BGN upon immersion in SBF for 14 days according to the FTIR spectrum (Fig.…”
Section: In Vitro Mineralizationsupporting
confidence: 69%
“…Alternatively, post modification of silica nanoparticles or binary BGN to introduce metallic ions has been shown to be able to avoid the aggregation of nanoparticles. 44,51 In this study, ZnO QDs were used as modification agents to introduce Zn ions. The modification was based on electrostatic interaction that could retain the structure and properties of the involved components.…”
Section: Discussionmentioning
confidence: 99%
“…Effectively, these materials were able to bond not only to bone, but to soft tissue as well, avoiding fibrous encapsulation. [5,16,17] Regarding the production of silver doped bioactive nanoparticles in the system SiO 2 -CaO-P 2 O 5 -Ag 2 O through the sol-gel methodology, some interesting works have been already developed with different silver contents. In fact, the implantation of materials for prostheses and tissue regeneration is often associated with the administration of antibiotics.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the implantation of materials for prostheses and tissue regeneration is often associated with the administration of antibiotics. On the other hand, some studies have reported that silver nanoparticles could induce some cytotoxicity effects, depending on the used concentration and on the culture time, typically at higher Ag contents, [14,16,20,21] in the present work our interest was focused on the development of an alternative and simple sol-gel methodology for the synthesis of new silicate glass nanoparticles with 10 mol% of silver oxide, using the same bioglass precursors described in a previous protocol developed and optimized by our group for a ternary bioglass system. [5] Ideally, the implant should have the ability to both regenerate bone tissue and to treat the infection by delivering an antibacterial agent in a controlled and continuous manner.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation